2008
DOI: 10.1148/radiol.2461061245
|View full text |Cite
|
Sign up to set email alerts
|

Double-Contrast Upper Gastrointestinal Radiography: A Pattern Approach for Diseases of the Stomach

Abstract: The double-contrast upper gastrointestinal series is a valuable diagnostic test for evaluating structural and functional abnormalities of the stomach. This article will review the normal radiographic anatomy of the stomach. The principles of analyzing double-contrast images will be discussed. A pattern approach for the diagnosis of gastric abnormalities will also be presented, focusing on abnormal mucosal patterns, depressed lesions, protruded lesions, thickened folds, and gastric narrowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…The greatest risk of follow-up observation without UGI-ES is to erroneously diagnose protruded early gastric cancers as nonmalignant gastric polyps, but our results indicate such misdiagnoses are quite rare. Nowadays, it has been gradually accepted that UGI-XR can detect not only gastric cancer but also premalignant atrophic/hypertrophic gastritis [4,25,30,32]. Our recent report demonstrated that UGI-XR can diagnose chronic H. pylori infection with very high accuracy (97.8 %; 1638 of 1674 subjects) [5].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The greatest risk of follow-up observation without UGI-ES is to erroneously diagnose protruded early gastric cancers as nonmalignant gastric polyps, but our results indicate such misdiagnoses are quite rare. Nowadays, it has been gradually accepted that UGI-XR can detect not only gastric cancer but also premalignant atrophic/hypertrophic gastritis [4,25,30,32]. Our recent report demonstrated that UGI-XR can diagnose chronic H. pylori infection with very high accuracy (97.8 %; 1638 of 1674 subjects) [5].…”
Section: Discussionmentioning
confidence: 93%
“…Since the 1960s, the UGI-XR-based gastric cancer screening program endorsed by the Japanese government has achieved a significant reduction in mortality and morbidity of gastric cancer [1][2][3]. UGI-XR can detect not only gastric cancer but also gastroduodenal erosion or ulcer, gastric or esophageal polyps, esophagogastric diverticula, atrophic or hypertrophic gastritis, esophageal hiatal hernia, and other lesions [4,5]. Of these various lesions, gastric polyp is one of the most frequent findings observed in the usual screening examination [6].…”
Section: Introductionmentioning
confidence: 99%
“…In Table S1, we provide all the data of our 962 study subjects, which include the Kimura-Takemoto classification of UGI-ES-based atrophic gastritis, the four-grade types of UGI-XR-based atrophic gastritis, serum titers of anti-H. pylori IgG, age, gender, body mass index, smoking history, alcohol use, serum pepsinogens, the ABCD risk classification of gastric cancer [9], the three-grade types of UGI-XR-based enlarged folds [24,25], etc. Extracted data of the 602 subjects without UGI-ES/UGI-XR-based atrophic gastritis and those of the 254 subjects with UGI-ES/UGI-XR-based atrophic gastritis are also provided in Tables S2 and S3.…”
Section: Discussionmentioning
confidence: 99%
“…By referring to several previous reports [23][24][25], we have recently established the four-grade classification of UGI-XR-based atrophic gastritis judging from the irregular shapes of areae gastricae and their expansion (normal, mild, moderate, and severe) [2]. These two categorizations of image-based atrophic gastritis and double/triple check of the images are minutely described in Fig.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Typical findings of gastritis include thin mucosal striations oriented perpendicular to the long axis of the gastric antrum, thickened rugal folds, and a granular appearance of the mucosa with numerous 1-to 2-mm mucosal nodules. 4 Peptic ulcers are mucosal defects that penetrate through the muscularis mucosa into the deeper layers of the gastric wall. These ulcers are demonstrated by either a focal barium pool within a depressed mucosal defect or a thin rim of barium outlining the margins of an unfilled ulcer.…”
Section: Discussionmentioning
confidence: 99%